Meningkatkan Keterampilan Berpikir Kritis, Komunikasi, dan Kolaborasi Muatan Matematika Menggunakan Kombinasi Model PSN Murid Kelas III SDN Seberang Mesjid 1 - Sofie Dhiya Maharani; Zain Ahmad Fauzi (Mataram University, 2026)
This study was motivated by the low levels of students’ critical thinking, communication, and collaboration skills in Mathematics learning. Students experienced difficulties in reasoning through problems, lacked confidence in expressing their opinions, and tended to be passive during group activities, resulting in low participation and learning outcomes. This study aimed to describe teacher activities and analyze the improvement of student activities, critical thinking skills, communication skills, collaboration skills, and learning outcomes through the combination of the Problem Based Learning (PBL), Student Teams Achievement Division (STAD), and Numbered Heads Together (NHT) models, hereafter referred to as the PSN model. This study employed a Classroom Action Research (CAR) approach conducted in three meetings involving 24 third-grade students of SDN Seberang Mesjid 1 Banjarmasin. Data were collected through observations of teacher activities, student activities, critical thinking, communication, and collaboration skills, as well as learning outcome tests. The results showed that the implementation of the PSN model improved the quality of learning in each meeting. Teacher activities reached the Very Good category with a percentage of 100%. Student activities increased from 33% to 92%. Critical thinking skills improved from 21% to 83%, communication skills from 25% to 83%, and collaboration skills from 29% to 92%. Classical learning outcomes also increased from 84% to 92%. Therefore, the combination of the PBL, STAD, and NHT models was effective in improving students’ activities, learning outcomes, and 21st-century skills.